Optimal body composition and anthropometric profile of world-class beach handball players by playing positions - Pueo, B.; Espina-Agullo, J. J.; Selles-Perez, S.; Penichet-Tomas, A. (Sustainability, 2020)
Profiling of beach handball players is required to optimize sports performance, talent identification, and injury prevention. The study aimed to describe the anthropometric characteristics, somatotype, and body composition of elite male and female beach handball players classified by playing positions. Thirty elite beach handball players (15 male, 15 female) of the Spanish National Beach Handball Team, which ranked fifth and first in the VII World Championships, respectively, were categorized as front (wings/specialists), back (pivots/defenders) players and goalkeepers. Independent from position, male players showed larger values of anthropometric characteristics, girths, breadths, and absolute components of body composition than female players. Contrastingly, skinfolds, and body fat mass percentage were higher in female players. All these results were statistically significant (p < 0.05) with large to extremely large effect sizes (d = 1.4-5.4). The position-related differences indicated that male back players were taller (p = 0.008; Etap2 = 0.56), heavier (p = 0.016; Etap2 = 0.50) and showed larger arm span (p = 0.036; Etap2 = 0.42) than front players. In contrast, female goalkeepers showed larger body mass (p = 0.007; Etap2 = 0.57) and BMI (p = 0.035; Etap2 = 0.43), whereas back players showed higher muscular mass than goalkeepers (p = 0.022; Etap2 = 0.47). The present study provides anthropometric reference values of elite beach handball players, and indicates differences between playing positions, providing normative data for talent identification of male and female players.